Design and control of a three-level solar inverter - Yat, Zhi Hao (Nanyang Technological University, 2023)
Solar inverters are essential to any clean energy source that generates a Direct Current (DC) to Alternating Current (AC) to enable the clean energy to be functional in homes and business. To provide better efficiency, three-level solar inverters are looked into in this study, to use an additional voltage level as compared to the two-level inverter, to produce outputs of better quality which results in a more efficient and reliable energy conversion process. It is especially crucial for solar energy systems where the maximum energy production is the best ideal scenario. For larger solar installations, three-level inverters are also capable of handling the higher voltage and power generated from the solar panels. In this study, the efficiency of three-level inverters is studied and analysed in comparison to two-level inverters.